2012 IEEE Global Communications Conference (GLOBECOM) 2012
DOI: 10.1109/glocom.2012.6503837
|View full text |Cite
|
Sign up to set email alerts
|

Exact outage probability of opportunistic DF relay systems with interference at both the relay and the destination over Nakagami-m fading channels

Abstract: In this paper, we investigate the outage behavior of a dual-hop opportunistic decode-and-forward (DF) relay system with co-channel interference (CCI) at both the relay and the destination. The source-relay and relay-destination channels as well as the interferers' channels at both the relay and the des tination nodes are assumed to follow Nakagami-m distribution.Exact closed-form expressions for the outage probability for both independent non-identically distributed (i.n.d.) and independent identically distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In the sequel, three representative works will be discussed. In [25], the outage behavior of dual-hop DF ORS schemes was investigated with CCI at both the relays and the destination. It was shown that the co-channel interferers do not affect the diversity gain.…”
Section: Introductionmentioning
confidence: 99%
“…In the sequel, three representative works will be discussed. In [25], the outage behavior of dual-hop DF ORS schemes was investigated with CCI at both the relays and the destination. It was shown that the co-channel interferers do not affect the diversity gain.…”
Section: Introductionmentioning
confidence: 99%
“…A key advantage of multihop wireless networks is their ability to connect a transmit source to a destination through multiple hops, thereby expanding the network coverage while alleviating the need for fixed infrastructure [1,2]. In addition, cognitive relaying networks (CRNs) are considered as one of the promising solutions for radio spectrum scarceness and bandwidth limitations.…”
Section: Introductionmentioning
confidence: 99%